(untitled) (Annals of Medical Research, 2023)
Aim: Respiratory syncytial virus is one of the most important causes of lower respiratory tract infections, with high mortality and morbidity in infants and children. It can cause airway inflammation, mucosal edema, and small airway collapse. Materials and Methods: We evaluated the clinical and demographic characteristics of newborns aged 0-30 days who were hospitalized in Yüzüncü Yıl University Neonatal Intensive Care Unit due to lower respiratory tract infections and whose respiratory syncytial virus test was positive between 15/December/2022 and 15/February/2023. Results: Between the specified dates, 29 patients diagnosed with lower respiratory tract infections were admitted to our neonatal unit. Of the oral/nasopharyngeal swab samples sent from all of these patients, one was positive for SARS-CoV-2, one for adenovirus, one for influenza A/B, and 18 (62%) respiratory syncytial virus. The weeks of the birth of the patients who were found to be positive for respiratory syncytial virus A/B were 36.72±1.48. The number of days they spent in the hospital was 6.72±1.6, 2(11.1%) patients required intubation, and 7(38.8%) patients required noninvasive respiratory support. One patient presented with convulsions at home, and cough and fever symptoms appeared on the second day of hospitalization. All patients recovered with oxygen support, hydration, and supportive treatment and were discharged. Conclusion: The most common cause in neonates was found to be a respiratory syncytial virus. Early diagnosis and treatment are important in patients with suspected lower tract viral infections. Unnecessary antibiotic use and the spread of the disease should be prevented by increasing access to viral tests.